Promoter polymorphism of the 5-HT transporter and Alzheimer's disease - Hu, Mei; Retz, Wolfgang; Baader, Miriam; Pesold, Brigitte; Adler, Georg; Henn, Fritz A.; Rösler, Michael; Thome, Johannes (Neuroscience letters, 2000)
The role of the deletion/insertion polymorphism within the promoter region of the serotonin transporter gene (5-HTT) is under discussion as a potential genetic risk factor for Alzheimers's disease (AD). Here we report significant differences in the allelic distribution of this polymorphism with a higher frequency of the short variant allele in AD patients when compared to controls. This difference was independent of the apolipoproteinE genotype. Thus, our study supports the notion that genetic alterations in the serontonergic neurotransmitter system may be involved in the etiopathogenesis of AD. However, given the reported negative findings, we are presently trying to identify diagnostic subgroups for which the 5-HTT promoter polymorphism represents a susceptibility locus.
Gesehen am 12.11.2020